Flypaper Effect pada PAD, Dana Perimbangan, & SiLPA terhadap Belanja Daerah - Dwi Suhartini; Putri Arimbi Nuritasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of Local Revenue, Balance Fund consisting of  General Allocation Fund and Special Allocation Fund, and Unspent Funds at End Final Year on Regional Expenditure in Central Java and Yogyakarta Special Region in 2017-2020. This study also examines whether the Flypaper Effect phenomenon occurs by comparing the Local Revenue coefficient with General Allocation Fund. This study uses quantitative methods and uses secondary data with a sample size of 44 Budget Realization Reports for four periods, namely 2017 - 2020. Testing in this study using eviews 10. Based on the results of this study, it shows that any increase in General Allocation Fund  and and Unspent Funds at End Final Year has an effect on the increase in regional expenditure, while the increase in Local Revenue and Special Allocation Fund does not affect the increase in regional expenditure. This study also found that local governments still depend on central government transfer funds, thus explaining the flypaper effect on local governments in Central Java and Yogyakarta Special Region in 2017-2020.